2021
DOI: 10.1186/s13063-021-05303-8
|View full text |Cite
|
Sign up to set email alerts
|

Comparative efficacy of a single-session “Empowered Relief” videoconference-delivered group intervention for chronic pain: study protocol for a randomized controlled trial

Abstract: Background Chronic pain is naturally aversive and often distressing for patients. Pain coping and self-regulatory skills have been shown to effectively reduce pain-related distress and other symptoms. In this trial, the primary goal is to pilot test the comparative efficacy of a single-session videoconference-delivered group pain education class to a waitlist control among patients with chronic pain. Methods Our study is a randomized clinical trial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 50 publications
0
9
0
Order By: Relevance
“…Although a growing body of research exists on the efficacy of ER for chronic and acute pain management [ 12 , 33 , 36 , 52 ], the use of Zoom as a platform to deliver behavioral medicine for chronic pain, particularly single-session treatment, remains novel and understudied. In addition, the extant literature on digital behavioral health research has reported participant treatment engagement rates ranging from 20% to 60% [ 33 , 84 - 86 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although a growing body of research exists on the efficacy of ER for chronic and acute pain management [ 12 , 33 , 36 , 52 ], the use of Zoom as a platform to deliver behavioral medicine for chronic pain, particularly single-session treatment, remains novel and understudied. In addition, the extant literature on digital behavioral health research has reported participant treatment engagement rates ranging from 20% to 60% [ 33 , 84 - 86 ].…”
Section: Discussionmentioning
confidence: 99%
“…The study coordinator (LGC) was unblinded to the individual study arm assignments and was not involved in any data analyses. The study protocol was reviewed and approved [ 52 ].…”
Section: Methodsmentioning
confidence: 99%
“…During the pandemic, a study proved that a single online intervention was able to reduce depression symptoms in adolescents under pandemic ( Schleider et al, 2022 ). In a study of chronic patients, online single-intervention groups were found to reduce negative emotions such as pain and anxiety, and depression in chronic patients ( Ziadni et al, 2021 ). A study found that a single online group psychological counseling session can effectively provide psychological support for the public and relieve psychological pressure under COVID-19 ( Ni et al, 2022 ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…For instance, effective single-session behavioral treatments could help address the needs of a population with pain. Indeed, four randomized trials have shown that singlesession treatments can substantially improve multidimensional chronic-pain outcomes (Carty et al, 2019;Darnall et al, 2021;Ziadni et al, 2018;Ziadni et al, 2021;Ziadni et al, in press). Clearly, brief interventions will be insufficient for some patients; however, they may be particularly convenient and feasible for many others.…”
Section: Solutions: Efficient and Scalable Treatmentsmentioning
confidence: 99%